Answer:
8?
Step-by-step explanation:
Step-by-step explanation:
First, replace f(x) with y ⇒ f(x)=6x-19 ⇒ y=6x-19
Then y with x and x with y ⇒ y=6x-19 ⇒ x=6y-19
Solve the equation from for y:
x=6y-19
x+19=6y dividing with 6
1/6 x +(19/6) = y
Replace y with f−1(x) ⇒ f−1(x)= 1/6 x +(19/6)
hope this helps!
There is no graph, so it is impossible to answer this question. I apologise.
Answer:−3K−395,−374,−198,−187
Step-by-step explanation:
Remove parentheses.
1−3K−396,0−374,0−198,0−187
Simplify 1-3K-3961−3K−396 to -3K-395−3K−395.
−3K−395,0−374,0−198,0−187
Simplify 0-3740−374 to -374−374.
−3K−395,−374,0−198,0−187
Simplify 0-1980−198 to -198−198.
−3K−395,−374,−198,0−187
Simplify 0-1870−187 to -187−187.
−3K−395,−374,−198,−187
Answer: Um, I think is
.
Step-by-step explanation: